Przyczynek do poznania potencjału mediów społecznościowych w edukacji leśnej - Lewoń, Radosław; Pirożnikow, Ewa (Leśne Prace Badawcze, 2019)
The development of social network sites not only facilitates the acquisition and deepening of knowledge, but also provides the possibility of easily contacting foresters, specialists in natural sciences and nature enthusiasts. In addition, for some years already, internet users have been able to make use of websites run by institutions and participate in nature-related social groups.The purpose of our survey was to evaluate the possibility of using the main fan page of the State Forests and virtual nature groups in Poland and Great Britain to propagate knowledge about nature and forestry. The aim was to verify the recipient groups and explore what benefits users derive from informal forest education as well as to determine how they assess the work of foresters or the reliability of the provided content posted on the portals.Studies have shown that the majority of respondents use portals to gain knowledge and communicate with specialists while social networks are the motivating factor encouraging people to take advantage of recreation in forest areas by collecting mushrooms and herbs. Our results clearly point out the advantages and disadvantages of the State Forests’ fan page and other nature–related social groups.The importance of social networks in the education and communication with the public is steadily increasing. Therefore, social network websites should be refined and accommodate the constantly-changing needs of society as well as allowing members of virtual groups to converse with foresters. The State Forests should support nature-related groups in attracting real enthusiasts. Organizational and substantive support for these groups would allow an increase in ecological awareness and gain of knowledge about forest management directly from practitioners.